2014
DOI: 10.4143/crt.2014.050
|View full text |Cite
|
Sign up to set email alerts
|

Previous Bladder Cancer History in Patients with High-Risk, Non–muscle-invasive Bladder Cancer Correlates with Recurrence and Progression: Implications of Natural History

Abstract: PurposeThe purpose of this study was to assess the correlation of previous bladder cancer history with the recurrence and progression of patients with high-risk non–muscle-invasive bladder cancer treated with adjuvant Bacillus Calmette–Guérin (BCG) and to evaluate their natural history.Materials and MethodsPatients were divided into two groups based on the existence of previous bladder cancer (primary, non-primary). A logistic regression analysis was used to identify the possible differences in the probabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, our patient had not received any anti-cancer treatment except for TUR of low-grade UC. It has been reported that past history of non-invasive cancer correlates with the malignant grade in secondary UC [ 11 ]. In addition, the role of inflammation in urothelial cell carcinogenesis has lately been receiving considerable attention [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our patient had not received any anti-cancer treatment except for TUR of low-grade UC. It has been reported that past history of non-invasive cancer correlates with the malignant grade in secondary UC [ 11 ]. In addition, the role of inflammation in urothelial cell carcinogenesis has lately been receiving considerable attention [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent endoscopic resection of the bladder tumour under spinal anesthesia. Three weeks postoperatively they initiated adjuvant intravesical therapy of either BCG or epirubicin instillations on an outpatient basis, as described elsewhere (14).…”
Section: Methodsmentioning
confidence: 99%
“…16,17,21,22,[24][25][26][27][28]31,[33][34][35][36][37]40,42,49,51,54,56,57,61,65,68,74,75,77 Among the remaining eight studies, rates of BCG induction therapy ranged from 29% to 95%. 20,45,47,52,59,63,77,78 The use of maintenance BCG in HR-NMIBC was reported in 31 studies, with rates being more variable than those seen with induction therapy. 16,17,[26][27][28][29]31,33,34,36,37,40,42,45,46,[49]…”
Section: Treatment Patternsmentioning
confidence: 99%
“…37,42,58 The use of re-TURBT in patients with HR-NMIBC was reported in 43 studies. 16,[18][19][20][21][22][23][27][28][29][30][31][32][33]37,[41][42][43]45,47,[49][50][51][52][53][54][55][56]58,64,69,70,74,77,78,[83][84][85][86][87][88][89][90] Across 27 studies, the use of this procedure varied from 15% to 82%, 16,18,[20][21][22][30]…”
Section: Treatment Patternsmentioning
confidence: 99%